The history of the representation concept: an artistic experience and psychic dynamism - Moreno, André Luiz (2013)
This study aims to understand how the historical concept of representation and its relationship with individual differences permeates the relationship between psychology and the theory of art in the history of philosophy. The research was conducted on texts by authors who discuss the psychic dynamism periods in the history of philosophy, represented by Plato, Aristotle, Augustine and theorists of Renaissance art. The analysis categories were defined after contact with the sources, to the extent that it became possible to locate the set of ideas of each author corresponding to the concept of representation. We conclude that each author constructs particular explanations for the modern concept of representation, each proposition concept has implications for understanding the psychic dynamism for each author.